(untitled) (LACCEI, 2024)
Currently, online assessments are booming. However, not everything is perfect. It is known that not having the possibility to supervise them has created a dilemma for teachers. The research describes university teacher’s experiences with virtual assessments, therefore, investigating biometric systems used as a remote proctoring system that verifies and monitors the student body while taking online exams is important for improving educational processes. The research with a qualitative approach interviewed ten university professors with more than five years of experience. A duly validated interview guide was prepared, meeting the quality criteria, in order to deepen the teachers’ answers. The quality criteria included credibility, transferability, reliability-confirmability and reflexibility. A mandatory inclusion criterion was to have experience in the use of systems such as Procterizer during online evaluations. The interview guide was distributed in two categories: online assessment and proctored tests. Likewise, a group discussion was held with five education professionals, in such a way that new categories were generated the results indicate that the student body develops multiple dishonest activities, plagiarism, examination with the help of third parties, payment to relatives, strangers, or group mates, who try to cheat to pass a course that they consider demanding. In conclusion, teachers have turned to new ways of controlling online evaluations to reduce the levels of plagiarism and generate the development of competencies in students